Liquid-Phase Back mixing in Bubble Columns - Burhan S. Abdulrazzaq (Tikrit Journal of Engineering Sciences, 2010)
Liquid-phase axial dispersion coefficients have been measured for air-water system in bubble columns of 10, 15 and 30 cm diameter. The experiments are carried out using a transient method (the tracer response method).  Dispersion coefficient is obtained by adjusting the experimental profiles of tracer concentration with the predictions of the model. The experimental results show that one-dimensional axial dispersion coefficient, Dax,L, reveal strong scale dependence. Backmixing of liquid phase increases with the increase of reactor diameter and superficial gas velocity.  Axial dispersion coefficient for large column reactors can be easily predicted from the developed relation . Comparison of calculated with the experimental data and with the published data of other authors shows good agreement which ensure the reliability and confusability of the adopted correlations to be used in further design and scale-up purposes.